SYSTEMATIC REVIEW OF THE USABILITY EVALUATION METHODOLOGY OF HEALTH INFORMATION SYSTEMS - Rivai Endra Dwi Yulianto; Susi Ari Kristina; Anna Wahyuni Widayanti (Jurnal Farmasi Sains dan Praktis, 2022)
A good information system will support the implementation of the tasks and functions of the organization. This systematic review aims to identify and characterize the methods and attributes in usability evaluation and identify measurement techniques in usability evaluation. This systematic review uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. The search was carried out using two databases, namely PubMed and Science Direct, by limiting information systems related to health published from 2015 to 2021. Articles that met the criteria were evaluated for methods, attributes, measurement techniques, and usability criteria used. Article quality was assessed using a modified Downs and Black checklist. The search identified 132 articles. The results of abstract screening and duplication-checking obtained 128 articles. The screening was carried out through a complete review of the inclusion and exclusion criteria, obtained 9 articles that met the criteria. There are five methods used for usability evaluation, namely Think aloud (TA), Heuristic evaluation (HE), System Usability Scale (SUS), User viewpoint, and Cognitive Walkthrough Method. Six problem definitions used in usability evaluation are ISO, Nielsen, user-based, TAUCHI, 19 item usability questions, and successful completion of scenarios. The measurement technique is done by qualitative and quantitative analysis. Effectiveness, efficiency, and satisfaction are criteria that are always assessed from almost all articles reviewed. The heuristic evaluation method with quantitative measurement techniques using an evaluator in evaluating usability based on scenarios then proceeding with qualitative measurement techniques to deepen problems and provide solutions is the most ideal usability evaluation measurement technique.